Silicide formation during Mn doping of Ge/Si (001) self-assembled quantum dots. Issue 23 (6th December 2013) - Kassim, J.; Nolph, Christopher A.; Jamet, Matthieu; Reinke, Petra; Floro, Jerrold A.
Abstract: Abstract : Heteroepitaxial Ge quantum dots were grown on Si (001) by molecular beam epitaxy, with a Mn co-deposition flux giving a nominal composition of Ge0.9 Mn0.1 . At this large Mn flux, and with growth temperatures of 450 °C required for Ge quantum dot self-assembly, extensive second phase formation occurred. Atomic force microscopy reveals that quantum dots typical for the Ge/Si (001) system still form. In addition, copious formation of both rod-like and cluster-like morphologies is observed, with many of these structures conjoined to Ge dots. Extensive transmission electron microscopy identified several coexisting intermetallic phases, all based on Mn–silicide crystal structures, albeit with varying degrees of Ge substitution. The Ge quantum dots themselves appear to have little or no Mn incorporated in them, indicating that the intermetallic particles scavenge Mn from extended surface areas. Under these growth conditions, Mn is highly mobile, with surface diffusion lengths of the order of 800 nm, with significant bulk mobility as well, resulting in surface structures that also penetrate the Si substrate. A magnetic phase transition at 220 °C does not match known behavior of the bulk silicide phases but might result from extensive ternary alloying with Ge, especially into the cubic MnSi phase.